Studi Kasus Resiliensi Transgender Penderita HIV AIDS di Lembaga Swadaya Masyarakat Keluarga Besar Waria Yogyakarta - Manik Muthmain; Indra Wahyudi; Wahyu Widiantoro (Jurnal Psikologi, 2022)
This research aims to describe the process of resilience of transgender people with HIV / AIDS in KEBAYA NGO. Transgender people often experience rejection, discrimination, stress, depression, are prone to suffering from sexually transmitted diseases and HIV / AIDS. This makes transgender people experience a downturn. The focus of this research is to find out how transgender people with HIV / AIDS are able to perform resilience. This research is a qualitative research with a case study approach. This study used two transgender informants with HIV / AIDS in the NGO KEBAYA. Data collection methods using observation, interview and triangulation techniques. The interview guide used was an adaptation of the CD - RISC (Connor-Davidson Resillience Scale) scale which has been translated and developed by the researcher. The results of this study indicate that the two transgender informants with HIV / AIDS in KEBAYA NGO are able to perform resilience. This is based on the analysis of the results of observations, interviews and triangulation. Both transgender people with HIV / AIDS have five factors on the CD-RISC scale, so they can be considered resilient individuals.